EVALUATION OF ALFALFA LEAF-PROTEIN-CONCENTRATE AS FEED FOR CLARIAS LAZERA (PISCES: CLARIIDAE) - AFOLABI, O. A.; OSUNTOGUN , B. A.; OSUNTOGUN , B. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Alfalfa (Medicago satival) leaf-protein-concentrate (LPC) was chemically and biologically evaluated as a feed for Clarias lazera. Based on proximate composition values alone, it could be concluded that LPC diet used was suitable for a high protein demanding such as C. lazera. However, the growth performance of C. lazera during the feeding trial presented PLC interior to the control which is a fishmeal-based diet. Toxic principles identified included saponin, alkaloids, tannins and phytate. A supplementation of the LPC diet with lysine and methionine improved the growth performance of the LPC by 419%. Organ index showed that while the liver and the gills were not affected by the LPC diets. kidney, heart and spleen were slightly enlarged. The experiment demonstrate that I-PC is inferior to fishmeal-based diets. However, LPC may be an alternative to fishmeal for herbivorous fishes or even C. lazera in the face a dwindling purchasing power of the developing world.